PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN REPUTASI PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Nur Afifah; Sri Wibawani Wahyuning Astuti; Dwi Irawan (EKUITAS (Jurnal Ekonomi dan Keuangan), 2021)
This study aims to provide empirical evidence about the effect of corporate social responsibility disclosure and corporate reputation on firm value. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018. The sample in this study was 120 companies selected through purposive sampling. The results of data analysis show that CSR has a negative effect on firm value. But the company's reputation has a positive effect on the value of the company. This study also examines the impact of CSR disclosure on company value mediated by company reputation, the results show that company reputation does not mediate CSR disclosure on company value. This finding shows that CSR activities and company reputation are very important for the company's survival. A good relationship between the company and its stakeholders, especially the community in the form of Corporate Social Responsibility activities and a reputation that has been built by a company, will increase the value of a company which is reflected in the stock price which is formed by the demand and supply of the capital market that reflects the public's assessment of the company's performance.